MEDIATION EFFECTS OF WORK MOTIVATION: The Influence of Competence, Organizational Communication and Role Conflict on Employee Performance - Kamalia (Scientia Integritas Utama, 2022)
This study aims to know Effect of Competence, Organizational Communication and Role Conflict on Employee Performance mediated by Work Motivation. To implement these objectives the data collection techniques are used through observation, questionnaires and documentation, using validity test analysis techniques, reliability testing, data analysis techniques, path analysis and sobel test. The results showed that competence had a positive and significant effect on employee performance, organizational communication had a positive and significant effect on employee performance. role conflict has a negative and significant effect on employee performance. work motivation has a positive and significant effect on employee performance. competence can increase motivation that has an impact on employee performance, work motivation can mediate the effect of organizational communication on employee performance. Mediation test results influence the role of conflict on employee performance through work motivation which shows that role conflict can explain the low level of work motivation so that the impact on declining performance the employee.